2019
DOI: 10.1111/jon.12599
|View full text |Cite
|
Sign up to set email alerts
|

The Role of CT Perfusion in Defining the Clinically Relevant Core Infarction to Guide Thrombectomy Selection in Patients with Acute Stroke

Abstract: BACKGROUND AND PURPOSE Infarct core assessment on presentation is important to evaluate salvageable tissue to select patients for thrombectomy. Our study aims to evaluate the correlation between infarct core volume measured by computed tomography (CT) perfusion (CTP) and magnetic resonance diffusion‐weighted imaging (MR‐DWI) in patients with acute large‐vessel occlusion. METHODS We studied patients who underwent CTP on presentation to the emergency department for stroke symptoms. National Institute of Health S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…26 False overestimation of infarct core is rare. 27 Recent studies have shown that penumbral profile on CTP is a better predictor of outcome as compared to ischemic changes on NCCT and collaterals on CTA even within the early (0-6 hours) treatment window and is a better modality for patient selection. [25][26][27][28] Recent studies have suggested superiority of MRI in assessing ischemic core as compared to CTP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26 False overestimation of infarct core is rare. 27 Recent studies have shown that penumbral profile on CTP is a better predictor of outcome as compared to ischemic changes on NCCT and collaterals on CTA even within the early (0-6 hours) treatment window and is a better modality for patient selection. [25][26][27][28] Recent studies have suggested superiority of MRI in assessing ischemic core as compared to CTP.…”
Section: Discussionmentioning
confidence: 99%
“…27 Recent studies have shown that penumbral profile on CTP is a better predictor of outcome as compared to ischemic changes on NCCT and collaterals on CTA even within the early (0-6 hours) treatment window and is a better modality for patient selection. [25][26][27][28] Recent studies have suggested superiority of MRI in assessing ischemic core as compared to CTP. [29][30][31] However, subgroup analyses from SWIFT-PRIME (early window) and DEFUSE III (late window) studies did not show a difference in outcome for CTP versus MRI selected patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A search of the references of included studies and previous systematic reviews [17, 18, 20, 21] identified 4 additional studies. A total of 167 full-text papers were reviewed and 48 studies [8, 12‒14, 29‒72] met the inclusion criteria (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%